2001
DOI: 10.4141/s00-071
|View full text |Cite
|
Sign up to set email alerts
|

Impact of long-term cultivation on the status of organic matter and cadmium in soil

Abstract: Research has suggested a link between the bioavailability of soil Cd and total soil organic matter. However, some research suggested a negative relationship between total soil organic matter and bioavailable soil Cd while other research suggested a positive relationship. This study investigated the relationship between soil Cd and both the quantity and quality of soil organic matter as influenced by long-term cultivation. Two Orthic Chernozemic surface soil samples, one from a virgin prairie and the other from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…The significant increase in aromaticity of the organic matter as a result of long-term cultivation appears to be the result of the cultivation enhanced degradation of aliphatic relative to aromatic C. Charcoal formed by crop residue burning may also contribute to the increased aromaticity; charcoal produces a large peak in the aromatic regions of 13 C NMR spectra (Golchin et al, 1997a,b;Schmidt et al, 1999;Skjemstad et al, 1996Skjemstad et al, , 1999aPonomarenko and Anderson, 2001). Increasing aromaticity of soil organic matter with prolonged cultivation was also reported by Schulten et al (1995), Lessa et al (1996), Kiem et al (2000), and McArthur et al (2001). …”
Section: Resultsmentioning
confidence: 60%
See 2 more Smart Citations
“…The significant increase in aromaticity of the organic matter as a result of long-term cultivation appears to be the result of the cultivation enhanced degradation of aliphatic relative to aromatic C. Charcoal formed by crop residue burning may also contribute to the increased aromaticity; charcoal produces a large peak in the aromatic regions of 13 C NMR spectra (Golchin et al, 1997a,b;Schmidt et al, 1999;Skjemstad et al, 1996Skjemstad et al, , 1999aPonomarenko and Anderson, 2001). Increasing aromaticity of soil organic matter with prolonged cultivation was also reported by Schulten et al (1995), Lessa et al (1996), Kiem et al (2000), and McArthur et al (2001). …”
Section: Resultsmentioning
confidence: 60%
“…It has been found that long-term cultivation results in a statistically significant decrease in the total amount of SOM (soil organic matter) (Blank and Fosberg, 1989;Schulten et al, 1995;Kiem et al, 2000;McArthur et al, 2001). As well, it has been shown that the aromaticity of the SOM increases as a result of long-term cultivation Lessa et al, 1996;Kiem et al, 2000;McArthur et al, 2001).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Tillage mainly changed the environment for micro-organisms and distribution of SOC to affect SOC concentration, thus long-term tillage resulted in a significant loss of total soil organic matter (McArthur et al, 2001). However, some reports agreed with the inverse result, that is, an increase of SOC concentration was observed in PT vs. NT systems (e.g.…”
Section: Tillage Impacts On Socmentioning
confidence: 99%
“…Soil organic matter, clay content, Fe, Al, and Mn oxides may increase the adsorption of Cd by soils and thus decrease soil Cd plant availability (McLaughlin et al 1996;McArthur et al 2001). Soil P, K, and S may increase Cd availability through different mechanisms McLaughlin et al 1996;Grant et al 1998).…”
Section: Tuber CD Concentration and Some Selected Soil Characteristicsmentioning
confidence: 99%